Interactive Theatre: Liberating employee-driven innovation. Issue 9 (5th August 2014) - Totterdill, Peter; Exton, Rosemary
Abstract : Purpose: – This paper aims to discuss how Interactive Theatre can be implemented and it also gives examples of it in action with feedback from clients. Unlocking employee creativity is one of the key challenges of implementing organisational change to improve performance and enhance working life. Design/methodology/approach: – Interactive Theatre is a dynamic event that helps to release employee inhibitions that prevent them from expressing their views while engaging them in critical reflection and creative thinking through facilitated dialogue and collaboration. Findings: – Using theatre to dramatise the issues and situations created by poor work organisation, inadequate skills and ineffective management practice encourages employers and employees alike to take action. Drama reveals all the tensions and problems that can exist in the business, while at the same time being fun and captivating. As a result, people are more likely to have an open mind about the need for change and to become actively involved in its design and implementation. Originality/value: – This paper discusses how Interactive Theatre can be implemented and gives examples of it in action with feedback from clients.